2005
DOI: 10.1111/j.1537-2995.2005.04350.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a new pathogen‐reduction technology (Mirasol PRT) on functional aspects of platelet concentrates

Abstract: PLT function was well preserved in PCs treated with 6.2 J per mL Mirasol PRT and stored for 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
105
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(126 citation statements)
references
References 41 publications
19
105
0
2
Order By: Relevance
“…Values obtained from other studies (n = 18) after initial prolonged resting time (study II/II/IV) showed non-significant increases in p-selectin expression in T-PC compared to C-PC. In addition, we found higher baseline expression of CD62p throughout storage, which is comparable to published results on PRT-treated platelets [4,[10][11][12]. Values observed in these studies range from 35% (day 1) up to 60% (day 5), which is comparable to our values of 23% (day 1) to 35% (day 5) in series I and of 28% (day 1) to 45% (day 6) in series IV.…”
Section: Discussionsupporting
confidence: 81%
“…Values obtained from other studies (n = 18) after initial prolonged resting time (study II/II/IV) showed non-significant increases in p-selectin expression in T-PC compared to C-PC. In addition, we found higher baseline expression of CD62p throughout storage, which is comparable to published results on PRT-treated platelets [4,[10][11][12]. Values observed in these studies range from 35% (day 1) up to 60% (day 5), which is comparable to our values of 23% (day 1) to 35% (day 5) in series I and of 28% (day 1) to 45% (day 6) in series IV.…”
Section: Discussionsupporting
confidence: 81%
“…1 To minimize contamination of blood platelets, several pathogen reduction approaches have been developed that rely on irradiation with ultraviolet light (UV) in combination with a photosensitizer. [2][3][4] Recently, the possibility of using UV-C light without the addition of an exogenous sensitizer has been explored. 5,6 This approach uses UV-C at a wavelength of 254 nm, which is highly absorbed by nucleic acids, resulting in cyclobutane pyrimidine dimer formation and DNA degradation.…”
mentioning
confidence: 99%
“…However, shearinduced adhesion is maintained in Mirasol-treated platelets [41][42][43], and mitochondrial function is preserved [44,45]. De- Overview of the Mirasol ® Pathogen Reduction Technology System 13 tween the Mirasol-treated and control group were detected for mean number of days between transfusions, mean number of platelet transfusions per patient and dose of platelets transfused.…”
Section: Mirasol Prt System For Plateletsmentioning
confidence: 99%